Atsar Wasilah TTS (Al-Kalimah Al-Mutaqatiah) Fi Itqani Al-Mufradat Lada Thalabah As-Shaf As-Sabi Fi Al-Madrasah Al-Tsanawiyah Al-Ahliyah PSA Sulit Air - Isra Hayati; Muhammad Basyiruddin (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The use of learning media in this growing era is certainly very much needed. Media are devices and tools used by a teacher to improve the teaching and learning process.  As we can see, there still many Arabic teacher only use the blackboard as a medium for teaching. This is one of factors that make students feel bored in learning. Crossword puzzles are one of the language game media that can be use in the teaching and learning process of Arabic. This language game media can make the learning process more varied and easy for students to understand. This study aims to determine the effect of using crossword puzzles of vocabulary mastery of class VII students at Mts.S PSA Sulit Air. This type of research is field research. While the methode used in this study is a quantitative research methode. The research design is a quasi-experimental design in the form of a nonequivalent control design. As for the research instrument in the form of pre-test, post-test question, and documentation. The form of data analysis that has been is the normality test, homogenity test and T-test using SPSS 21.  Data analysis showed that the average value of the pre-test was 65,46 and the post-test was 88,67. It means that there is an increase in the value of 23,21. And it can be concluded that the use of crossword puzzles has an effect on vacabulary mastery of calss VII students at Mts.S PSA Sulit Air.